Efektifitas penggunaan model pembelajaran kooperatif dengan presentasi untuk meningkatkan kemampuan belajar menulis surat kelas XI PM di SMK Negeri 48 - Rahayu Retno Pujiastuti (Jurnal Ilmiah Econosains, 2016)
ABSTRACT This study aims to Know Efekifitas use Cooperative Learning Model Type Presentation Can Improve Learning Ability Letter Writing Class XI PM at SMK Negeri 48 2014. The experiment was conducted in July to / with December 2014, in SMK Negeri 48 Jakarta. Learning Model for this use is Cooperative Presentation mode, Class Action Research, which consists of two cycles, each cycle of meetings held three times and at the third meeting done Post Test. Indicators of success seen improved understanding of the concept, kreaktifan, and decrease the negative habits of students during the learning process. The instrument used in this study was a test sheet and Observation class observing aspects of liveliness and negative habits. Research has achieved the expected indicators in the second cycle, the number of students who scored to complete the boundary or over by 97, 45% and the average reached 80, 79%. Key words: cooperative learning model, enhance learning in class XI wrote, class action research